1997
DOI: 10.1097/00000539-199707000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid Excretion Increases During Propofol Anesthesia

Abstract: We compared the effect of propofol with that of sevoflurane anesthesia on uric acid (UA) excretion in ASA physical status I and II patients with normal renal function. A propofol group (n = 11) received propofol-nitrous oxide-fentanyl after induction of anesthesia by propofol, while a sevoflurane group (n = 12) received sevoflurane-nitrous oxide-fentanyl after induction of anesthesia by thiamylal. UA, creatinine (Cr), and urea nitrogen concentrations in serum and urine were measured before induction of anesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…[18] Propofol increases urine uric acid excretion and is beneficial for such patients. [19] Succinylcholine is preferably avoided because of abnormal potassium influx. [20] Atracurium is safe for muscle relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Propofol increases urine uric acid excretion and is beneficial for such patients. [19] Succinylcholine is preferably avoided because of abnormal potassium influx. [20] Atracurium is safe for muscle relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Masuda et al [6] observed that uric acid excretion increased during anesthesia using propofol by inhibiting uric acid reabsorption similar to probenecid. Therefore, increased uric acid excretion due to the administration of propofol is believed to be an important factor in urine color changes.…”
Section: Discussionmentioning
confidence: 99%
“…Not all patients administred propofol exhibit urine discoloration. Masuda et al [6] suggested that crystal development is closely related to urine pH and temperature, in addition to urine uric acid concentration. It is known that uric acid is precipitated in an acidic urine pH and at low temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Masuda et al .,[6] in their study of 23 patients, performed a urine analysis of all patients undergoing surgeries with TIVA ( n =11) and sevoflurane ( n =12) anaesthesia. They inferred that all patients on TIVA had increased urine uric acid.…”
mentioning
confidence: 99%
“…Milky color urine is observed more frequently in operation theatres with ambient temperature less than 24°C. [6] The reason attributed to this is that decreased temperature causes decreased solubility to uric acid crystals.…”
mentioning
confidence: 99%